Zakat Hasil Tangkapan Laut dalam Pemahaman Juragan Nelayan dan Elaborasinya pada Hukum Islam - Khasiatilah; Eka Suriansyah; Muhammad Norhadi (QISTHOSIA : Jurnal Syariah dan Hukum, 2024)
This research was motivated by the lack of understanding of fishermen on the obligation to pay zakat of the sea product. Although the income of the employer nelayan has been categorized as compulsory zakat, it turns out that most of the employers still did not pay zakat. There are two purposes of the study were to determine the implementation of paying zakat of the sea product in Sungai Cabang Barat Village and to find out the understanding of fishermen on zakat of the sea product. This research used a socio-legal approach. Data collection techniques carried out in research were by interviews, observation, and documentation. The subjects of the study were five fishermen who owned boats and employees to go to sea.  There are two theories used in research, namely urf’ theory, maslahah mursalah theory, and sociological theory of knowledge.  The results showed that: (1) the comprehension of fishermen in Sungai Cabang Barat Village on the obligation to pay zakat of the sea product, including the following:  some knew and carried out the obligation of zakat of the sea product, some did not know at all, and some just knew but did not pay zakat. (2) the implemented of paying zakat of the sea product in Sungai Cabang Barat village, including the following: zakat was paid annually, usually zakat was cashed at the time before Eid al-Fitr. Zakat was distributed to the closest family, but these relatives were indeed included in the category of mustahiq zakat. Nishab zakat of the sea product followed to zakat trade and zakat mal. The fishermen paid and distributed his zakat directly to mustahiq without going through the amil agency.